Evaluation of the potential impact of a carbapenem de-escalation program in an academic healthcare system - Farah Ahmad; Jason M. Pogue; Dror Marchaim; Teena Chopra; Suchita Bheemreddy; Jiha Lee; Niveditha S. Mudegowdra; Aaisha Chaudhry; Keith S. Kaye (Elsevier, 2014)
Summary: The primary objective of this analysis was to evaluate group 2 carbapenem usage and to model the impact that a formalized de-escalation protocol to ertapenem could potentially have on group 2 carbapenem usage in the hope of alleviating the selective pressure on Acinetobacter and Pseudomonas. This analysis was conducted in three hospitals within the Detroit Medical Center in 2009. Patients were considered candidates for de-escalation of carbapenem therapy when a group 2 carbapenem was utilized to treat Enterobacteriaceae, such as extended spectrum β-lactamase (ESBL)-producing organisms, or if cultures were negative in non-intensive care unit (ICU) patients. In total, 179 patients (28%) and 1074 patient-days (29%) were deemed eligible for de-escalation according to our pre-defined criteria. We concluded that preferential utilization of ertapenem in appropriate patients warranting carbapenem therapy has the potential to significantly decrease group 2 carbapenem usage at our institution. Keywords: Ertapenem, De-escalation, Streamlining, Antimicrobial stewardship, Carbapenem